The Effectiveness of WhatsApp Group–Based Media in Preparing Cervical Cancer Patients for Their First Chemotherapy - Anastasia Ning Minarsih (LPPM Widyagama Husada Malang, 2026)
Cervical cancer is the second largest cancer in women and is the leading cause of death in developing countries. From a preliminary study at RSUD dr. Saiful Anwar Malang, an average of 60 new patients per month will undergo chemotherapy, 30 people (50%) of whom cannot make a decision when the doctor will give chemotherapy because of the patient's unpreparedness in terms of knowledge, physical, psychological, and lack of family support. The purpose of this study is to determine the effectiveness of whatsapp group media on cervical cancer patients in preparing for first chemotherapy at RSUD dr. Saiful Anwar Malang in 2025.This study used a one group pre test post test design research method. The sample was taken by using accidental sampling, in which 44 respondents on November 28 - December 28, 2024 were given educational intervention in the form of Whatsapp Group. After being given an educational intervention with Whatsapp Group, the results of the analysis test with the paired-T Test obtained knowledge readiness p-value 0.003 with the correlation of 0.340, so that whatsapp7 group is effective in knowledge readiness. physical readiness p-value 0.002 with the correlation of 0.450, so that whatsapp group is effective in physical readiness. psychological readiness p-value 0.005 with the correlation 0.262, so that whatsapp group is effective in psychological readiness. Family support readiness p-value 0.004 with the correlation 0.524, so it can be concluded that whatsapp group is effective in realizing family support readiness and it is also effective in supporting the readiness of cervical cancer patients in facing their first chemotherapy. References (2014 - 2023).